Novel microfluidic devices for aerosol analysis - Mentele, Mallory M., author; Henry, Charles, advisor; Barisas, George, committee member; Reynolds, Melissa, committee member; Ladanyi, Branka, committee member; Kreidenweis, Sonia, committee member (Colorado State University. Libraries, 2012)
Widespread interest in microfluidic technology over the past 20 years has led to the development of microfluidic devices that are as varied in their complexity and capabilities as they are in the applications they are used for. This dissertation describes the development of two microfluidic devices, each designed for measurement of specific aerosol components. A microchip incorporating an interface between a continuous hydrodynamic sample flow and capillary electrophoresis separation was developed for analysis of atmospheric aerosols. The ability to separate and detect analytes from a continuous sample flow allows the microchip to be coupled to a particle-into-liquid aerosol sampler, providing a method for near real-time analysis of ionic aerosol components. Theoretical modeling of hydrodynamic and electroosmotic flows was used to predict flow behavior in the microchip and to optimize geometry. Separation and conductivity detection of common ionic aerosol components were carried out to observe device performance, and detection of nitrate and sulfate in Fort Collins air was accomplished with the coupled system. The simple design introduced here is the first example of a continuous flow microfluidic capillary electrophoresis device that incorporates conductivity detection, and is the first microfluidic device to be coupled to a continuous flow aerosol collector. A paper-based microfluidic device was also designed for the purpose of assessing occupational exposure to particulate metals. Assays were developed for colorimetric detection of metals on paper and these were employed in detection reservoirs of the device. A novel method was also developed for rapid digestion of particulate metals directly on a filter. Metal concentrations were quantified from color intensity images using a scanner in conjunction with image processing software. Finally, a standard incineration ash sample was aerosolized, collected on filters, and analyzed for the three metals of interest. This is the first paper-based device capable of multiplexed metal detection from a real, aerosolized sample.
Keywords: aerosols; microfluidics